PREVALENCE AND RISK FACTOR OF CHILDHOOD ASTHMA AND ALLERGIC DISEASE FOR POPULATION LIVING IN THE NEIGHBORHOOD OF CEMENT FACTORY EMISSION - Finny Fitry Yani; Dhyna Lidya Lestari; Husna Yetti; Rizanda Machmud (Jurnal Kesehatan Masyarakat Andalas, 2020)
Prevalence of asthma in children increase especially in the industrial city. Cement factory in Padang city is located near from community, cause air pollution, especially to children. We aim to know the prevalence and risk factor of asthma and allergic disease in this area. A cross sectional study to children age 0-15 years old has been done on May-June 2015, around the Cement factory, with distance from factory <5 km (exposed area) and >10 km (un-exposed area). We used International Study of Asthma and Allergy in Childhood (ISAAC) questionnaire to determine asthma and allergic disease. Data was taken from the parent about asthma, allergic rhinitis and atopic dermatitis symptoms and some risk factors. Data was analyzed with chi-square test. This study found 90 children, 43 (47.8%) from exposed area. Asthma prevalence and atopic dermatitis was found higher in un-exposed area than exposed area (19.5% vs 13.9% and 39.1% vs 37.2%), allergic rhinitis was higher in exposed area (60.4% vs 58.6%), though no significance difference. This study concluded that there were no significant differences in asthma and allergies disease in exposed and un-exposed area of semen factory emissions.